Відповідь:
1) 9+13х=35+26х;
13х-26х=35-9
-13х=26
х=26:(-13)
х=2
2) -5х+2=-10х;
-5х+10х=-2
5х=-2
х=-2:5
х=-0,4
3) -7х-7=4-8х;
-7х+8х=4+7
х=11
4) 2(х-7)=3;
2х-14=3
2х=3+14
2х=17
х=17:2
х=8,5
5) 7(х-1)=3х;
7х-7=3х
7х-3х=7
4х=7
х=7:4
х=1,75
6) 4(х+6)=х;
4х+24=х
4х-х=-24
3х=-24
х=-24:3
х=-8
7) 7(-3+2х)=-6х-1
-21+14х=-6х-1
14х+6х=-1+21
20х=20
х=20:20
х=1
Відповідь:
1) 9+13х=35+26х;
13х-26х=35-9
-13х=26
х=26:(-13)
х=2
2) -5х+2=-10х;
-5х+10х=-2
5х=-2
х=-2:5
х=-0,4
3) -7х-7=4-8х;
-7х+8х=4+7
х=11
4) 2(х-7)=3;
2х-14=3
2х=3+14
2х=17
х=17:2
х=8,5
5) 7(х-1)=3х;
7х-7=3х
7х-3х=7
4х=7
х=7:4
х=1,75
6) 4(х+6)=х;
4х+24=х
4х-х=-24
3х=-24
х=-24:3
х=-8
7) 7(-3+2х)=-6х-1
-21+14х=-6х-1
14х+6х=-1+21
20х=20
х=20:20
х=1